Two new species of the genus Foenobethylus Kieffer 1913 (Hymenoptera: Bethylidae) from China with a key to the known species - Liu, Jingxian; Chen, Huayan; Xu, Zaifu (Zootaxa, 2011)
The genus Foenobethylus Kieffer 1913 is newly recorded from China. Two species: F. hainanensis sp. nov. (Hainan) and F. zhejiangensis sp. nov. (Zhejiang) are described and illustrated. A key to the world species of the genus is provided.